Pengembangan E-Modul Berbasis PBL dengan Pendekatan STEM Pada Materi Ciri-Ciri Hewan, Tumbuhan, dan Habitatnya untuk Siswa Kelas VI Sekolah Dasar - Annisa Yola Shafarina; Vera Yuli Erviana (JURNAL INOVASI DAN MANAJEMEN PENDIDIKAN, 2022)
This research is motivated by the use of learning media which is still limited, and only school textbooks that do not prioritize the development of students' problem solving abilities are used. This study aims to understand the steps of developing the modular characteristics of animals, plants and their habitats and to determine their quality. This development research uses the ADDIE model (analysis, design, development, implementation, and evaluation). The objects of this research are material expert teachers, media experts, linguists, learningÂ experts and sixth grade teachers at SD Negeri Kalongan. Data collection techniques in the form of assessment. Quantitative and qualitative data analysis was used to evaluate teaching materials. This research develops modules on the characteristics of animals, plants and their habitats. The results showed that the quality of material experts was in the appropriate category, with an average score of 3.2. The quality assessment carried out by a linguist in the appropriate category had a mean score of 3.0. The quality assessment carried out by media experts using the very appropriate category has an average score of 3.4. The quality assessment carried out by learning experts has a very user-friendly category with an average score of 3.3. The teacher assesses the quality in the very appropriate category, with an average score of 3.8. These results indicate that the quality of the module is included in the very feasible category to be used as teaching materials.